Juridical Review Of Minor Marriage Dispensation - Annisa Ayu Martiana (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Law Number 16 of 2019 which amends the old Marriage Law changes the marriage age limit for women and men to 19 years. So if you are less than 19 years old you are required to go through the marriage dispensation stage at the court. It is known that the marriage dispensation issued by the religious court plays a very important role in carrying out the legal process for underage marriages. In the decision of case number 138/Pdt.P/2022/PA.Kdr, the judge granted the request for a marriage dispensation letter due to the urgent situation that the prospective wife was 4 months pregnant. The research method used in this writing is a qualitative research method with descriptive analysis methods and accompanied by a normative juridical approach. The results of this research explain the conditions that must be fulfilled by the parties to obtain dispensation and analysis of determination number 138/Pdt.P/2022/PA.Kdr.